KAJIAN PERILAKU PRAGMATIS TERHADAP TINDAK TUTUR SANTRI TERHADAP KYAI DI PONDOK PESANTREN DI WILAYAH KOTA SEMARANG - Tiani, Riris (HUMANIKA, 2016)
The main study is speech of moslem students assessed by using pragmatics approach that is politenes principle. Indicator in every maxim of politenes principle is used as santri having (sermon) in front of others santri. The goal of the research is to describe about the implementation of politenes principle maxims and to determine the politenes of santri’s speech delivering their sermon to others santri. The result of data analysis found the applications of tive maxims in Leech politenes principle on santri’s speech of the sermon. Its also found the determinant factor of politenes namely linguistics factors and nonlinguistics factors. Linguistics factors was found diction application and style of santri’s speech. Meanwhile, nonlinguistics factors was found that senior santri’s were more in applicating politenes maxim rather than junior santri’s. In addition, the use foreign language such as Arabic.